2015
DOI: 10.14802/jmd.15031
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Age-Related Striatal Dopamine Depletion in Parkinson’s Disease

Abstract: ObjectiveGender differences are a well-known clinical characteristic of Parkinson’s disease (PD). In-vivo imaging studies demonstrated that women have greater striatal dopamine transporter (DAT) activity than do men, both in the normal population and in PD patients. We hypothesize that women exhibit more rapid aging-related striatal DAT reduction than do men, as the potential neuroprotective effect of estrogen wanes with age.MethodsThis study included 307 de novo PD patients (152 men and 155 women) who underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Because the MOCA survey is more time consuming than age determination, age was retained and MOCA excluded. Finally, nine factors described as possible dysphagia risk factors were included in the analysis, the scale and coding of which are given in brackets: age (years), gender (male = 0, female = 1), BMI (metric), affirmed subjective aspiration signs ("no" = 0, "yes" = 1), NMS‐Quest 3 ("no" = 0, "yes" = 1), MDS‐UPDRS III score (metric), BDI‐II score (metric), DBS (absent = 0, present = 1), and disease duration (years). The binary logistic regression analysis showed that affirmed subjective aspiration signs, gender, and higher age were significantly associated with the risk of critical aspiration (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Because the MOCA survey is more time consuming than age determination, age was retained and MOCA excluded. Finally, nine factors described as possible dysphagia risk factors were included in the analysis, the scale and coding of which are given in brackets: age (years), gender (male = 0, female = 1), BMI (metric), affirmed subjective aspiration signs ("no" = 0, "yes" = 1), NMS‐Quest 3 ("no" = 0, "yes" = 1), MDS‐UPDRS III score (metric), BDI‐II score (metric), DBS (absent = 0, present = 1), and disease duration (years). The binary logistic regression analysis showed that affirmed subjective aspiration signs, gender, and higher age were significantly associated with the risk of critical aspiration (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, numerous studies have tried to identify clinical findings associated with significant dysphagia. Clinical features that were found to be linked to significant dysphagia included age, gender, BMI, disease duration, disease severity, DBS, depression, and cognitive function . To assess the relative value of these clinical features, a regression analysis was performed in this study and suggested that the three parameters "affirmed subjective aspiration signs," "high age," and "gender" represent the strongest clinical criteria for predicting the risk of severe dysphagia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, some studies suggest that DA transporter availability may not differ between gender, nor across the menstrual cycle [Best et al, ]. However, other studies suggests that women may have greater DA transporter functioning in the dorsal striatum [Andersen et al, ; Kaasinen et al, ; Lee et al, ; Wong et al, ], as well as greater DA synthesis capacity in the caudate [Laakso et al, ]. While we used sex as a covariate in our main analyses, there may be important sex differences between D 2/3 R availability and brain morphology.…”
Section: Discussionmentioning
confidence: 99%